Guild Patterns of Basidiomycetes Community Associated With Quercus mongolica in Mt. Jeombong, Republic of Korea - Seung-Yoon Oh; Hae Jin Cho; John A. Eimes; Sang-Kuk Han; Chang Sun Kim; Young Woon Lim (Mycobiology, 2018)
Depending on the mode of nutrition exploitation, major fungal guilds are distinguished as ectomycorrhizal and saprotrophic fungi. It is generally known that diverse environmental factors influence fungal communities; however, it is unclear how fungal communities respond differently to environment factors depend on fungal guilds. In this study, we investigated basidiomycetes communities associated with Quercus mongolica using 454 pyrosequencing. We attempted to detect guild pattern (ectomycorrhizal or saprotrophic fungal communities) by comparing the influence of geography and source (root and surrounding soil). A total of 515 mOTUs were detected from root (321) and soil (394) of Q. mongolica at three sites of Mt. Jeombong in Inje County. We found that patterns of diversity and community structure were different depending on the guilds. In terms of alpha diversity, only ectomycorrhizal fungi showed significant differences between sources. In terms of community structure, however, geography significantly influenced the ectomycorrhizal community, while source appeared to have a greater influence on the saprotrophic community. Therefore, a guild-based view will help to elucidates novel features of the relationship between environmental factors and fungal communities.